Innovation and Ex Ante Consideration of Licensing Terms in Standard Setting - Tor Winston (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
In an effort to produce interoperable products, firms frequently participate in Standard Setting Organizations (SSOs) to collaboratively set technical standards for products used by networks of consumers. Some SSO members say they suffer from a type of holdup: after they sink technology-specific investments in developing and implementing a standard using a particular patented technology the patent owner can set licensing terms that exploit those investments. These members have called on SSOs to enhance competition between patent owners by soliciting and considering licensing terms for competing technologies ex ante, before anointing one as "the standard." However, more competitive licensing terms may dampen incentives to innovate. This paper analyzes the balance between the welfare benefits of the added competition and the welfare costs of reduced innovation. The model of R&D investment and standard setting predicts that both total welfare and consumer welfare are higher when an SSO considered licensing terms ex ante as long as the cost of innovation is not "high." The model also predicts that the welfare benefits of ex ante consideration of licensing terms grow as the costs of innovation falls. However, when the cost of innovation is "high" the negative welfare effects are always small.
Keywords: 330